Durability Design of Concrete Structures Under Reinforce-ment Corrosion - عبدالقوي علي الحاج (مجلة العلوم الهندسية والتقنية)
Traditionally, the durability design of concrete structures is based on implicit rules (minimum concrete cover, maximum water/cement ratio, crack width limitation, etc.). The research on concrete durability during the last decades has produced a reliable basis for information on deterioration processes. Based on this knowledge, it is possible to start incorporating durability in the design of concrete structures. Standard reliability methods were used to evaluate time dependent reliability of concrete structures under corrosion attack.